Rapid identification of clinically interesting methanogens using an improved MALDI-TOF-MS assay. Issue 7 (12th July 2022) - Guindo, Cheick Oumar; Amir, Lynda; Couderc, Carine; Drancourt, Michel; Grine, Ghiles
Abstract : Methanogens, the archaea uniquely detoxifying fermentative hydrogen into methane in the digestive tract, are increasingly being detected in pathology situations, rendering their rapid identification mandatory. We improved the experimental protocol to identify broth-cultured methanogens by matrix-assisted laser desorption time-of-flight MS (MALDI-TOF-MS). A database incorporating 34 reference spectra derived from 16 methanogen reference strains representative of eight species supported further identification of 21 Methanobrevibacter smithii and 14 Methanobrevibacter oralis isolates broth-cultured from human stool and oral fluid, respectively, with scores >2. In addition, MALDI-TOF-MS differentiated five Methanobrevibacter smithii genotypes incorporated in the study. The data reported here found MALDI-TOF-MS as a first-line identification method for methanogens recovered from microbiota and clinical samples.